Analytical performance of the Xpert Carba-R assay for direct detection of carbapenemase genes in respiratory specimens from hospitalized patients: a multicenter evaluation in China - Li, Keke; Liu, Yuling; Yao, Yihui; Wang, Jie; Hui, Yanxia; Li, Juan; Luo, Xiaoliang; Gao, Xinghui; Tang, Yi-Wei; Wei, Lianhua (Frontiers in Microbiology, 2025)
BackgroundRespiratory tract infections remain the main sites of carbapenem-resistant Enterobacteriaceae (CRE) infections in China and limited information on enzyme genotypes and subtypes in China is available. In this study, we used whole-genome sequencing (WGS) and the Xpert Carba-R assay for the detection, genotyping and subsubtyping of CRE genes from respiratory specimens collected from Southeast (Zhejiang, Jiangxi and Fujian Provinces) and Northwest (Gansu Province) regions of China.MethodsRespiratory specimens from hospitalized patients clinically diagnosed with pneumonia from seven tertiary hospitals in China from October 2022 to November 2023 were included. The CRE enzyme genes in specimens were directly detected and genotyped by using the Carba-R assay. Carbapenem resistance and genotypes were compared to a referee in combination of phenotypical and genotypical analyses of pure cultures recovered from the respiratory specimen. The CRE enzyme subtypes in isolates were determined by the WGS.ResultsA total of 433 respiratory specimens were collected and tested in this study. The Carba-R assay detected 180 blaKPC (41.3%), 64 blaNDM (14.8%), 5 blaIMP (1.2%), 4 blaVIM (0.9%), and 4 blaOXA-48 (0.9%) genes. In comparison to the above referee, the sensitivity and specificity of the Carba-R assay for CRE detection were 100 and 90.4%. While there were no genotype distribution differences between the Southeast and Northwest regions, more KPC subtypes were identified in the Northwest (n = 5) than Southeast (n = 2) region.ConclusionThe Carba-R assay satisfactorily detected and identified carbapenemase genes directly in the respiratory specimens. A variety of CRE enzyme genotypes and subtypes were identified in respiratory specimens especially the Northwest region of China.